2022
DOI: 10.1186/s13195-022-01130-4
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment needs of dementia with Lewy bodies according to patients, caregivers, and physicians: a cross-sectional, observational, questionnaire-based study in Japan

Abstract: Background Understanding the treatment needs of patients with dementia with Lewy bodies (DLB) is essential to develop treatment strategies. We examined the treatment needs of patients with DLB and their caregivers and the extent to which the attending physicians understand these treatment needs. Methods This was a cross-sectional, observational study conducted using questionnaires for patients, caregivers, and physicians. The study participants inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 36 publications
0
26
1
Order By: Relevance
“…This result was based on the evaluations by physicians who prescribed medication for autonomic dysfunction and focused on dysuria. This differs from the findings of the main study, 10 which analyzed all physicians enrolled in the study. Intervention of medications for dysuria may in themselves increase caregiver satisfaction, although their impact on the burden of caregiving was not evaluated in this study.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…This result was based on the evaluations by physicians who prescribed medication for autonomic dysfunction and focused on dysuria. This differs from the findings of the main study, 10 which analyzed all physicians enrolled in the study. Intervention of medications for dysuria may in themselves increase caregiver satisfaction, although their impact on the burden of caregiving was not evaluated in this study.…”
Section: Discussioncontrasting
confidence: 97%
“…The main study was conducted from September 2020 to July 2021 and the details of the study design have been previously reported 10 . This study was conducted at 35 facilities in Japan including university hospitals, non‐university hospitals, and clinics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following publication of the original article [ 1 ], the authors corrected “the patient” to “the caregiver” in Table 4 header.…”
mentioning
confidence: 99%